Seeing The World through Philadelphia The International City - Perry, Linda; World Affairs Council of Philadelphia, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
This student booklet provides an introduction to the city of Philadelphia and explores the city's global connections. The volume contains the following chapters: (1) "Philadelphia: The City of Neighborhoods"; (2) "International Visitors Enjoy Our Sights"; (3) "Foreign Students Make a Temporary Home With Us"; and (4) "Philadelphia and International Business." Map activities, a glossary of terms, and a six-item bibliography are included in the booklet. (EH)
Availability: World Affairs Council of Philadelphia, 1314 Chestnut Street, Philadelphia, PA 19107.
Students.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Area Studies; Cross Cultural Studies; Elementary Secondary Education; Geographic Location; Global Education; Human Geography; International Cooperation; Multicultural Education; Place of Residence; Site Analysis; Social Studies; Pennsylvania (Philadelphia); Guides, Classroom -- Learner